Nickel (II) Removal from Aqueous Solutions by Adsorption on Fly-ash. - Vishvakarma, Prem Prakash; Yavada, Kailash Prakash; Singh, Vishwanath (1989)
The feasibility of Ni(II) removal from water was investigated by adsorption on fly-ash. The equilibrium data of Ni(II) removal thus obtained is well fitted to Langmuir equation. The mono layer adsorption capacity was calculated and found to be 0.293 mg-1 at 30C. The batch adsorption kinetics follows first order reaction and appears to be diffusion controlled. The values of mass transfer and pore diffusion coefficients were 1.14 X 10-5 cm S-I and 6.2 xlO -1l cm2 s-J respectively at 30C. The influence of initial nickel concentration, residence time, temperature and pH on metal adsorption process was studied, An increase in the solution temperature, pH and decrease in concentration favour the removal of nickel by fly-ash. The maximum adsorption of Ni(II) ions was noted at pH 7.0. The various thermodynamic parameters were calculated for the present system. The empirical model has been tested for the kinetics join(II) removal by adsorption on fly ash and the parameters for the continuous operation of the removal process were determined.